2010
DOI: 10.5380/avs.v15i2.16155
|View full text |Cite
|
Sign up to set email alerts
|

PESQUISA DE ANTICORPOS CONTRA <i>Cysticercus bovis</i>, POR TESTE ELISA EM BOVINOS DE ABATEDOURO

Abstract: RESEARCH OF Cysticercus bovis ANTIBODIES BY ELISA TEST IN SLAUGHTERHOUSE ANIMALS ABSTRACT:In order to standardize a serological test for diagnosing cysticercosis in cattle, 812 animals have been tested, most of them halfblooded zebu cattle, males and females, from age groups ranging from 18 months to 60 months. The animals had come from 139 municipalities in the State of Parana. The animals were identified and slaughtered in a slaughterhouse in the metropolitan region of Curitiba/PR-Brazil. From the animals th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…Pinto et al (2006) tested the total antigen of Taenia crassiceps, and obtained a sensitivity of 90.0% with experimentally infected animals, using 2 SD as the cut-off point, demonstrating the acceptable performance of ELISA in the detection of antibodies in experimentally infected animals. Thomaz-Soccol et al (2010) obtained a better antigenic sensitivity (83.6%) for animals (bovines) naturally cysticercosis positive than that observed in this study. However, the sensitivity rates of both studies were higher than the sensitivity rates of post mortem inspections reported in previous studies (ABUSEIR et al, 2006;CALVO-ARTAVIA et al, 2012;EICHENBERGER et al, 2011;SCANDRETT et al, 2009).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Pinto et al (2006) tested the total antigen of Taenia crassiceps, and obtained a sensitivity of 90.0% with experimentally infected animals, using 2 SD as the cut-off point, demonstrating the acceptable performance of ELISA in the detection of antibodies in experimentally infected animals. Thomaz-Soccol et al (2010) obtained a better antigenic sensitivity (83.6%) for animals (bovines) naturally cysticercosis positive than that observed in this study. However, the sensitivity rates of both studies were higher than the sensitivity rates of post mortem inspections reported in previous studies (ABUSEIR et al, 2006;CALVO-ARTAVIA et al, 2012;EICHENBERGER et al, 2011;SCANDRETT et al, 2009).…”
Section: Discussioncontrasting
confidence: 53%
“…Ogunremi and Benjamin (2010) observed a similar specificity (90.6%) for bovines that tested negative for cysticercosis. Thomaz-Soccol et al (2010) also obtained a specificity of 92.8% with a 3 SD cut-off point, when analyzing sera from slaughtered cattle that tested negative for cysticercosis. Additionally, Geerts et al (1981) also obtained a high specificity (94.0%), revealing the detection of cysticercosis in two animals regarded as negative by post mortem inspection by ELISA; a more detailed examination of the carcass revealed that these animals were, in fact, infected with cysticerci.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the ELISA should be able to detect animals at different stages of infection (viable or non-viable cysticerci), and similarly, showing satisfactory performance (Pinto et al, 2006;Monteiro et al, 2006;Minozzo et al, 2004;Guimarães-Peixoto et al, 2015). According Smith et al (1991) low levels in low cyst-burden produced antibodies hinder the selection of a cutoff point and interpretation of findings in serological tests such as ELISA, especially in monocysticercosis (Thomaz-Soccol et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The main performance parameters (sensitivity and specificity) of the ELISA for animal cysticercosis diagnosis have been reported by several authors [ 3 , 8 11 ]. However, satisfactory results have not yet been obtained when naturally infected animals were the diagnostic target, because of the insufficient amount of circulating antibodies [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%